2018
DOI: 10.1155/2018/3479846
|View full text |Cite
|
Sign up to set email alerts
|

Croatian National Data and Comparison with European Practice: Data from the Cardiac Resynchronization Therapy Survey II Multicenter Registry

Abstract: Aims The Cardiac Resynchronization Therapy (CRT) Survey II was conducted between October 2015 and December 2016 and included data from 11088 CRT implantations from 42 countries. The survey's aim was to report on current European CRT practice. The aim of this study was to compare the Croatian national CRT practice with the European data. Methods Five centres from Croatia recruited consecutive patients, in a 15-month period, who underwent CRT implantation, primary or an upgrade. Data were collected prospectively… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…Such large emphasis on QRS morphology and duration is believed to be due to health care budget restrictions in Croatia. 52 Bulgaria, Croatia and Switzerland had lower percentage CRT-D than the total cohort. 52,55,57 The Croatian and Bulgarian implanters attribute this lower percentage to budgetary restriction; in Bulgaria CRT-D is not fully reimbursed and patients are not always able to afford co-payments for these devices.…”
Section: National Publications From Crt Survey IImentioning
confidence: 79%
See 3 more Smart Citations
“…Such large emphasis on QRS morphology and duration is believed to be due to health care budget restrictions in Croatia. 52 Bulgaria, Croatia and Switzerland had lower percentage CRT-D than the total cohort. 52,55,57 The Croatian and Bulgarian implanters attribute this lower percentage to budgetary restriction; in Bulgaria CRT-D is not fully reimbursed and patients are not always able to afford co-payments for these devices.…”
Section: National Publications From Crt Survey IImentioning
confidence: 79%
“…52 Bulgaria, Croatia and Switzerland had lower percentage CRT-D than the total cohort. 52,55,57 The Croatian and Bulgarian implanters attribute this lower percentage to budgetary restriction; in Bulgaria CRT-D is not fully reimbursed and patients are not always able to afford co-payments for these devices. Switzerland, on the other hand, has a reimbursement system that allows for easy access to available technology.…”
Section: National Publications From Crt Survey IImentioning
confidence: 79%
See 2 more Smart Citations
“…Epidemiological data show that almost 75% of patients with CIED will have an indication for MRI during their lifetime ( 1 ). With the increasing number of patients being implanted with CIEDs ( 2 , 3 ), in some of whom MRI may not be adequately replaced by other diagnostic imaging, there is the need for a standardized protocol for MRI imaging in these patients. Today, numerous studies have shown that it is possible and safe to use MRI in the large majority of CIED patients even up to 3T ( 4 - 7 ).…”
Section: Introductionmentioning
confidence: 99%